141k views
2 votes
In a triangle ABC, AD is drawn perpendicular to BC.
Prove that AB2 - BD2 = AC2 - CD2.

User Tryangul
by
6.4k points

1 Answer

4 votes

Answer:

Given: In triangle ABC , AD is drawn perpendicular to BC.

Since AD is drawn perpendicular to BC, it creates two right triangles: ADB and ADC.

Prove that:
AB^2-BD^2 = AC^2-CD^2

Pythagoras triangle for right angle, the square of the length of the hypotenuse is equal to the sum of the squares of the lengths of the legs.

In a right angle triangle ADB;


AD^2+BD^2 = AB^2 [By Pythagoras theorem]

or


AD^2= AB^2-BD^2 .......[1]

Now, in right angle triangle ADC;


AD^2+CD^2 = AC^2 [By Pythagoras theorem]

or we can write this as;


AD^2= AC^2-CD^2 ......[2]

Substituting the equation [1] in [2] we get;


AB^2-BD^2 =AC^2-CD^2 hence proved!

In a triangle ABC, AD is drawn perpendicular to BC. Prove that AB2 - BD2 = AC2 - CD-example-1
User Yabert Yanuar
by
6.1k points